Seasonal variation in nutritional value of variegated grasshopper Zonocerus variegatus in Abeokuta Ogun state Nigeria - AV, Adeniyi; KO, Ademolu; CI, Iyeh; AA, Osipitan; AB, Idowu (International Research Journal of Insect Sciences, 2024)
Zonocerus variegatus is a polyphagous species capable of consuming most of the plant species in its surroundings, climatic conditions and pesticide application have been reported to affect their natural life. In our locality, little or no information is available on the seasonal variation in the nutritional value of Zonocerus variegates. This study therefore evaluated the seasonal variation in the nutritional value of Z. variegatus in Abeokuta, Ogun state, Nigeria. Adult male and female Z. variegatus were collected during dry and wet seasons using a sweep net from an uncultivated farm at the Federal University of Agriculture, Abeokuta. Proximate composition, mineral composition, antinutrients, and vitamins) were determined using standard methods. All data collected were presented as Means±S.D. and compared using the T-test at (p < 0.05). Results showed that dry-season populations of Z. variegatus had significantly (p < 0.05) higher moisture content, crude protein, and carbohydrates than wet-season counterparts. Similarly, phosphorus concentration showed significant differences (p < 0.05) in the sample population for both seasons with the wet season population having higher values than the dry season. Vitamin A had a higher value (121.38 mg/100g) in the wet season than during the dry season (13,877 μg/100 g), while Vitamins D, B2, B6, and B12 values were higher during the dry season than in the wet-season. Antinutrient concentration was higher (p < 0.05) in the wet-season population than in the dry-season population. This study has shown that the dry-season Z. variegatus population is richer in nutrients than the wet-season population.